THE INFLUENCE OF HEDONIC SHOPPING MOTIVATION, SHOPPING LIFESTYLE AND SALES PROMOTION ON IMPULSIVE PURCHASE ON TOKOPEDIA INDONESIA E-COMMERCE CONSUMERS (CASE STUDY IN SURABAYA). - Yonathan, Irawan Adi (PERFORMA, 2022)
ABSTRACT With the development of internet technology makes human behavior change in shopping, that is, by online shopping, one of them is through E- commerce which keeps on increasing from year to year. With this, it is important for E-commerce companies to be able to study consumer behavior in making purchase decision in order to be able to increase the purchase number of company’s products. Without realizing it, there are a lot of E-commerce consumers do purchase suddenly without prior planning, that is, impulse purchase. This research focuses on the factors that influence impulse buying, that is, hedonic shopping motivation, shopping lifestyle and sales promotion. This research is done to find out the influence of Hedonic Shopping Motivation, Shopping Lifestyle and Sales Promotion on Impulsive Purchase on Tokopedia Indonesia E-commerce consumers. The research method uses quantitative method, by collecting research data with distributing questionnaires using Google Forms to 100 respondents who are Tokopedia E-commerce consumers that domicile in Surabaya. Using primary data source type is with non-probability sampling method with purposive sampling technique. Data analysis tool that is used is SPSS version 25. The result of this research shows that there is partial or simultaneous influence of Hedonic Shopping Motivation, Shopping Lifestyle and Impulsive Purchase variables on Tokopedia Indonesia E-commerce consumers. Keyword: Hedonic Shopping Motivation, Shopping Lifestyle, Sales Promotion, Impulsive Purchase.